Investigations on synchronization of a standalone microgrid system with main grid - Wang, Yingya (2016)
With the increasing demand for high-quality power and environmental-friendly resources, the microgrid technology has been investigated by many researchers. Microgrid is a small-sized power grid with local distributed generation. It is able to operate by connecting to the main grid or operate independently with its self-sustained power supply. This project aims to investigate the automatic seamless transition between the microgrid standalone mode and the grid-connected mode. Battery Management System is also implemented to enable the battery charging and discharging function depending on the power order and the state of charge (SOC). Furthermore, the proposed system can give commands for shedding loads based on the SOC. The control strategies for the PWM converter and the DC/DC converter are presented in the standalone mode, the grid-connected mode and the seamless transition between these two modes. The complete microgrid system is modeled in the MATLAB/Simulink and validated by performing tasks on the real-time simulation software, i.e OPAL-RT/RT-LAB.